Comparison of simultaneous invasive and non-invasive measurements of blood pressure based upon MIMIC II database - Bing Liu; Peng Qiu; Hong Chen; Qiao Li (Artery Research, 2014)
Objective: To compare the simultaneous invasive and non-invasive measurements of blood pressure (IBP and NIBP) based upon the Multiparameter Intelligent Monitoring in Intensive Care II (MIMIC II) database. Methods and results: A total of 986 records and 26,942 blood pressure (BP) measurements were extracted from MIMIC II database. The mean values of invasive systolic and invasive diastolic blood pressure (ISBP and IDBP) were 111.2 ± 33.9 mm Hg and 59.9 ± 22.8 mm Hg respectively, and the values of non-invasive ones were 114.0 ± 23.4 mm Hg and 51.0 ± 14.9 mm Hg. The average differences of systolic and diastolic blood pressure were −2.8 mm Hg and 8.9 mm Hg between IBP and NIBP. The correlation coefficients were 0.60 between ISBP and NISBP and 0.45 between IDBP and NIDBP. The robust regression equations between IBP (y) and NIBP (x) showed y = 1.02x − 2.95 for SBP (R2 = 0.60) and y = 0.77x + 18.43 for DBP (R2 = 0.82). At the higher part of BP, IBP is larger than NIBP, and at the lower part of BP, IBP is less than NIBP. Conclusion: Average invasive systolic blood pressure is lower than the non-invasive one and average invasive diastolic blood pressure is higher than the non-invasive one. The IBP shows good correlation with the NIBP. The invasive blood pressures can be estimated from non-invasive ones by the regression equations.